The effect of a self-modelling video intervention on motor skill acquisition and retention of a novice track cyclist's standing start performance - Jennings, C.; Reaburn, P.; Rynne, S. (International Journal of Sports Science and Coaching, 2013)
The purpose of this study was to examine the effectiveness of a video-self modelling intervention on the cycling standing start performance and self-efficacy beliefs of novice track cyclists. Nineteen participants from a Talent Identification Program were randomly assigned to one of two groups (Traditional and Intervention group). The traditional group received verbal augmented feedback, whereas the intervention group received a self-modelling video intervention in addition to verbal augmented feedback. Analysis of post-test and retention test scores revealed that both groups improved their performances and self-efficacy beliefs over time, but no significant interaction or difference existed between the groups. Future research is recommended with longer interventions and an emphasis on the editing of technique errors from the self-modelling video.